Thioredoxin-1 Is a Target to Attenuate Alzheimer-Like Pathology in Diabetic Encephalopathy by Alleviating Endoplasmic Reticulum Stress and Oxidative Stress - Guo, Yu; Zhang, Chenghong; Wang, Chunyang; Huang, Yufei; Liu, Jingyun; Chu, Haiying; Ren, Xiang; Kong, Li; Ma, Haiying (Frontiers in Physiology, 2021)
Varying degrees of central nervous system neuropathy induced by diabetes mellitus (DM) contribute to a cognitive disorder known as diabetic encephalopathy (DE), which is also one of the independent risk factors for Alzheimer's disease (AD). Endoplasmic reticulum stress (ERS) plays a critical role in the occurrence and development of DE and AD. However, its molecular mechanism remains largely unknown. This study aims to investigate whether thioredoxin-1 (Trx-1) could alleviate DE and AD through ERS, oxidative stress (OS) and apoptosis signaling pathways. Mice were randomly divided into a wild-type group (WT-NC), a streptozotocin (STZ)-treated DM group (WT-DM), a Trx-tg group (TG-NC) and a Trx-tg DM group (TG-DM). Diabetic animals showed an increase in the time spent in the target quadrant and the number of platform crossings as well as AD-like behavior in the water maze experiment. The immunocontent of the AD-related protein Tau and the levels of cell apoptosis, β-amyloid (Aβ) plaque formation and neuronal degeneration in the hippocampus of the diabetic group were increased. Some key factors associated with ERS, such as protein disulfide isomerase (PDI), glucose-regulated protein 78 (GRP78), inositol-requiring enzyme 1α (IRE1α), tumor necrosis factor receptor-associated factor 2 (TRAF2), apoptosis signal-regulating kinase-1 (ASK1), c-Jun N-terminal kinase (JNK), protein kinase RNA (PKR)-like ER kinase (PERK), and C/EBP homologous protein (CHOP), were upregulated, and other factors related to anti-oxidant stress, such as nuclear factor erythroid 2-related factor (Nrf2), were downregulated in the DM group. Moreover, DM caused an increase in the immunocontents of caspase-3 and caspase-12. However, these changes were reversed in the Trx-tg DM group. Therefore, we conclude that Trx-1 might be a key factor in alleviating DE and AD by regulating ERS and oxidative stress response, thus preventing apoptosis.